Is the effect of a political event more pronounced for government controlled firms? - Irwan Trinugroho; Aurio Fajrin; Sutaryo Sutaryo (Journal of Economics, Business, and Accountancy Ventura, 2016)
This study investigates market reaction to a political event, which is the presidential election of Republic of Indonesia in 2014 by studying 387 publicly traded firms in the Indonesia Stock Exchange. It employs event study method to measure the information content of this event. By going deeper, this study looked at the effect difference between government controlled firms (partially privatized firms) and private firms. The results show that there was a significant abnormal return around the event date. The negative abnormal return one day before the election date, which was followed by rebounding one day after the event, indicate that investors consider that the election had been done well particularly with respect to the political stability and security. Moreover, this paper reveals that the effect of presidential election is more pronounced for government-controlled firms than private firms. Government controlled firms may be more susceptible to political event.